2016
DOI: 10.1128/aac.00318-16
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Active Anti-Hepatitis C Virus Metabolites of 2,6-Diaminopurine Ribonucleoside Prodrug Compared to Sofosbuvir and BMS-986094

Abstract: bRibonucleoside analog inhibitors (rNAI) target the hepatitis C virus (HCV) RNA-dependent RNA polymerase nonstructural protein 5B (NS5B) and cause RNA chain termination. Here, we expand our studies on ␤-D-2=-C-methyl-2,6-diaminopurine-ribonucleotide (DAPN) phosphoramidate prodrug 1 (PD1) as a novel investigational inhibitor of HCV. DAPN-PD1 is metabolized intracellularly into two distinct bioactive nucleoside triphosphate (TP) analogs. The first metabolite, 2=-C-methyl-GTP, is a wellcharacterized inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Consistent with these observations, Arnold et al reported that increased POLRMT incorporation of NAI-TPs, as well as high intracellular NAI-TP levels, correlated positively with reductions in mitochondrial RNA levels and cytotoxicity (14). Similarly, we recently showed that treatment of Huh-7 cells with BMS-986094, which generates high levels of 2=-C-methyl-GTP intracellularly, inhibited mitochondrial RNA transcription (17). Interestingly, treatment with a 2,6-diaminopurine nucleotide (DAPN) prodrug, an investigational anti-HCV agent that also generates 2=-C-methyl-GTP (18), did not have similar deleterious effects.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Consistent with these observations, Arnold et al reported that increased POLRMT incorporation of NAI-TPs, as well as high intracellular NAI-TP levels, correlated positively with reductions in mitochondrial RNA levels and cytotoxicity (14). Similarly, we recently showed that treatment of Huh-7 cells with BMS-986094, which generates high levels of 2=-C-methyl-GTP intracellularly, inhibited mitochondrial RNA transcription (17). Interestingly, treatment with a 2,6-diaminopurine nucleotide (DAPN) prodrug, an investigational anti-HCV agent that also generates 2=-C-methyl-GTP (18), did not have similar deleterious effects.…”
supporting
confidence: 77%
“…Interestingly, treatment with a 2,6-diaminopurine nucleotide (DAPN) prodrug, an investigational anti-HCV agent that also generates 2=-C-methyl-GTP (18), did not have similar deleterious effects. Lower levels of intracellular NAI-TP accumulation were proposed to account for the distinct cytotoxicity profiles of these compounds (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We next evaluated the intracellular metabolism of NHC. We incubated a 10 M or 50 M concentration of the NHC parent nucleoside in Huh-7 cells essentially as described previously (20). Briefly, Huh-7 cells were seeded at 1 ϫ 10 6 cells per well in 12-well plates and incubated with NHC for 4 h. Cells were subsequently washed and analyzed using liquid chromatography-tandem mass spectroscopy (LC-MS/MS).…”
mentioning
confidence: 99%